Experimental Investigation of Additive Manufacturing of Continuous Carbon Fiber Composites with Multifunctional Electro-Tensile Properties - Ritesh Ghimire (MDPI AG, 2021)
Manufacturing processes for monofunctional and multifunctional materials vary depending on the design optimization. Multifunctional continuous carbon fiber composites provide great potential in achieving coupled structural and electrical properties for their applications in aircraft, unmanned aircraft systems, and spacecraft. Proper optimization of tensile and electrical properties offers benefits early in the design and continuous operational safety phases to obtain coupled multifunctional properties. In this paper, fused filament fabrication additive manufacturing (AM) technique was used to fabricate continuous carbon fiber solid laminated composites test coupons. The proposed new method characterizes the electrical conductivity’s coupled effects on the tensile properties, including the failure loads and modes. This paper addresses a novel way of integrating electrical function into the composites that significantly reduce weight, potentially replacing the bulky electrical wires. Tensile and electrical conductivity tests were concurrently conducted on coupons, and the results were plotted and tabulated. The results showed the multifunctional properties of the maximum ultimate tensile strength of 392 MPa with the maximum tensile load of 8907 N, and resistance of 37.5 G·Ω. The average values for ultimate tensile strength and maximum load were 371 MPa and 8459 N, respectively.